An energy‐efficiency‐adaptive clustering formation mechanism for the wireless sensor networks. Issue 3 (8th February 2022) - Lin, Deyu; Kong, Linghe; Zhao, Chengkun; Gao, Jiayi; Ouyang, Hao; Yang, Ziyuan; Zhang, Zhiqiang
Abstract: Energy inequality caused by the process of cluster head election has a large influence on energy efficiency and the network lifetime of wireless sensor networks (WSNs). To this end, a novel concept of EIec is proposed to evaluate the equality degree of energy consumption. Related theorems for establishing the candidate set of cluster heads are proposed, with the aim of promoting energy equality in each cluster. Subsequently, a novel energy‐efficiency‐adaptive cluster formation mechanism based on economic (ECFE) theory is proposed and detailed. Finally, extensive experiments are carried out to assess its energy efficiency and the network performance by comparisons with the existing classic and latest intelligent clustering algorithms. The results indicate that ECFE improves not only the energy efficiency but also the network performance effectively.